A sequence is defined recursively by f(0)=2 and f(n)=f(n+1)=-2f(n)+3 for n greater than or equal to 0, then f(2) is equal to

Answers

Answer 1
Answer:

If you would like to know what is f(2), you can calculate this using the following steps:

f(0) = 2
f(n+1) = - 2 * f(n) + 3
f(1) = - 2 * f(0) + 3 = - 2 * 2 + 3 = - 4 + 3 = - 1
f(2) = - 2 * f(1) + 3 = - 2 * (-1) + 3 = 2 + 3 = 5

The correct result would be f(2) = 5.


Related Questions

Please help! What is the value of B in the following proportion? 11/12 = B/156A. 24B. 143C. 134D. 170
What does 100%, 4/4 ,1.000 have in common
Blain exchanges $100 for yen before going to Japan. If each U.S. dollar is worth 88.353 yen, how many yen should Blain receive?
length of a room is 3 times its breadth and height is 4.6 m.if the total cost of carpeting the floor of a room at the rate of Rs. 60 per square meter is Rs. 4500,Find the total cost of papering the 4 walls at the rate of Rs. 6.​
A 2-yard piece of aluminum wire costs $17.16. What is the price per foot? PLS ANSWER!!!!

The table shows the outputs y for different inputs x:Input
(x) 2 4 6 8
Output
(y) 1 2 3 4


Part A: Do the data in this table represent a function? Justify your answer. (3 points)
Part B: Compare the data in the table with the relation f(x) = 3x – 10. Which relation has a greater value when x = 8? (2 points)
Part C: Using the relation in Part B, what is the value of x if f(x) = 80? (5 points)

PLEASE HELP!!!!!!!!!!!

Answers

A.   The data in the table represent a function. y=x/2. This is seen as for every value of x in the table, y=x/2(half of it). You can show this further by trying this fact on each value.

B.   For the original function, when x =8, y=x/2=4
For the function given in this part, when x=8, y=3(8)-10
                                                                 y=24-10                                                                                                            y=14
     This means the relation given in this part has a greater value when x=8

C. When x=80, f(x)=3(80)-10
                           =240-10
                           =230 

What is the ratio 35:5 in simplest form?

Answers

35:5 <=> \boxed{7:1}
It would be 7:1 because you divide each side by 5.

How long will it take a seal swimming at a speed of 8 miles per hour to travel 52 miles?

Answers

6.5 hours. The reason being is that i did 8x6, and got 48, then realized that another .5 would get me 48+4=52, which would fufill the equation

8x6.5=52 
Answer: 6.5 Hours 

Answer:6.5


Step-by-step explanation:


LessonNavigatorPrintFeedback5. what is the volume of the cube?9 in9 in

Answers

the volume of the cube is 
v = Sx3
v=9x9x9
v=729

All quadrilaterals are parallelograms

Answers

This statement is false. Parallelograms are four-sided figures that have two sets of parallel sides. A quadrilateral is simply a four-sided figure. The sides may be any length and at any angle from one another. So all parallelograms are quadrilaterals, but only some quadrilaterals are parallelograms.
Hope that helped! =)

The statement is true on apex, just took the test so I know.

A portion of the Quadratic Formula proof is shown. Fill in the missing reason. Statements Reasons ax2 + bx + c = 0 Given ax2 + bx = −c Subtract c from both sides of the equation x squared plus b over a times x equals negative c over a Divide both sides of the equation by a x squared plus b over a times x plus the quantity b over 2 times a squared equals negative c over a plus the quantity b over 2 times a squared Complete the square and add the quantity b over 2 times a squared to both sides x squared plus b over a times x plus the quantity b over 2 times a squared equals negative c over a plus b squared over 4 times a squared Square the quantity b over 2 times a on the right side of the equation x squared plus b over a times x plus the quantity b over 2 times a end quantity squared equals negative 4 times a times c over 4 times a squared plus b squared over 4 times a squared Find a common denominator on the right side of the equation x squared plus b over a times x plus the quantity b over 2 times a squared equals b squared minus 4 times a times c all over 4 times a squared Add the fractions together on the right side of the equation quantity x plus b over 2 times a end quantity squared equals b squared minus 4 times a times c all over 4 times a squared ? Rewrite the perfect square trinomial as a binomial squared on the left side of the equation Take the square root of both sides of the equation Multiply both sides of the equation by 2 Square the left side of the equation

Answers

Answer:

Find a common denominator on the right side of the equation

Step-by-step explanation:

I was taking the test and couldn't find the answer to this question anywhere so let me help you out...  

abidemiokin provided a wonderful step-by-step explanation for solving the formula, but left out the actual answer for the question which is what I'm here for. I read through abidemiokin's explanation and reviewed my options before choosing the best answer. As you see in step 5 of my edited version of abidemiokin's explanation the missing step is there. In the provided question we see steps 1,2, 3, and 4 being identical to those in the explanation below. From this, it is clear the next step (step 5) would be the next step, and as it is one of the options we can trust that it is correct.

(If you still have doubts then trust the fact that I took the test and the answer I provided above was indeed correct.)

Given the quadratic equation ax²+bx+c = 0, to derive the quadratic formula from the equation, the following steps must be followed;

ax²+bx+c = 0

Step 1: Subtract c from both sides

ax²+bx+c-c = 0-c

ax²+bx = -c

Step 2: Divide both sides of the equation by a

ax²/a + bx/a = -c/a

x² + bx/a = -c/a

Step 3: Complete the square and add the quantity (b/2a)² times a squared to both sides

x² + bx/a +  (b/2a)² = -c/a +  (b/2a)²

Step 4: Square the quantity  b/2a on the right side of the equation

x² + bx/a +  (b/2a)² =  -c/a +  b²/4a²

Step 5: Find a common denominator on the right side of the equation which is 4a²

x² + bx/a +  (b/2a)² =  -4ac/4a² +  b²/4a²

Step 6: Add the fractions together on the right side of the equation

x² + bx/a +  (b/2a)² =  (-4ac+  b²)/4a²

Note: The fraction at the right-hand side of the equation is to be added together not multiplied as shown in the question.

Step 7: The equation on the left is to be written as a perfect square as shown

(x+b/2a)² =  (-4ac+  b²)/4a²

Step 8: Take the square root of both sides

√(x+b/2a)² = √ (-4ac+  b²)/4a²

(x+b/2a) =  √(-4ac+  b²)/2a

Step 9: subtract b/2a from both sides

x+b/2a - b/2a =  -b/2a + √(-4ac+  b²)/2a

x =  -b/2a + √(-4ac+  b²)/2a

Step 10: Add the fractions together on the right-hand side

x =  -b±√(-4ac+  b²)/2a

This gives the required equation

Answer: A  Find a common denominator on the right side of the equation

Step-by-step explanation: Took the test of FLVS